A study on embodied carbon transfer at the provincial level of China from a social network perspective. (10th July 2019) - Lv, Kangjuan; Feng, Xia; Kelly, Scott; Zhu, Lei; Deng, Maozhi
Abstract: This paper incorporates the multiregional input-output (MRIO) and social network analysis (SNA) methods to investigate China's embodied carbon transfer across provinces. We estimate the amount of interprovincial embodied carbon transfer from 2002 to 2012, analyse the spatial correlation network structure of carbon transfer and its determinants. Our work can clarify the spatial distribution and different roles of provinces in the carbon transfer network. The empirical results show the spatio-temporal evolution of embodied carbon transfer; in 2002, embodied carbon transfer occurred from the energy-rich northern provinces to the developed eastern and central provinces, but in 2012, it transferred to developing southwestern and southern provinces. Moreover, the northwestern provinces act as "bridges" between the central and eastern provinces; eastern provinces play a "bidirectional spillover" role that transfers carbon internally and externally. The embodied carbon transfer network proposed here can help policy makers further clarify individual provinces' carbon emissions reduction responsibilities and curb national carbon emissions. Highlights: The spatial correlation network structure of embodied carbon transfer in China is analysed. The carbon emissions is with obvious regional disequilibrium and the transfer is "geographic adhesiveness". Northwestern provinces act as "bridges" meanwhile Eastern provinces play a "bidirectional spillover" role in carbon transfer. The environmental path dependence is most important in affecting embodied carbon transfer in 2012.